Highly efficient adsorption of ciprofloxacin from aqueous solutions by waste cation exchange resin-based activated carbons: Performance, mechanism, and theoretical calculation - Li, Qiang; Li, Haochen; Zong, Xiaofei; Sun, Haochao; Liu, Yunhao; Zhan, Ziyi; Mei, Shou; Qi, Yanjie; Huang, Yangbo; Ye, Yuxuan; Pan, Fei (The Science of the total environment, 2024)
This study focused on the preparation of a highly efficient activated carbon adsorbent from waste cation exchange resins through one-step carbonization to remove ciprofloxacin (CIP) from aqueous solutions. Scanning electron microscopy, X-ray diffraction, Fourier-transform infrared spectrometry, and X-ray photoelectron spectroscopy were used to characterize the physicochemical properties of the carbonized materials. The CIP removal efficiency, influencing factors, and adsorption mechanisms of CIP on the carbonized resins were investigated. Density functional theory (DFT) computations were performed to elucidate the adsorption mechanisms. The CIP removal reached 93 % when the adsorbent dosage was 300 mg/L at 25 °C. The adsorption capacity of the carbonized resins to CIP gradually decreased with an increasing pH from 3.0 to 7.0 and sharply declined with a pH from 7.0 to 11.0. The adsorption process better fitted by the pseudo second-order kinetic and Langmuir models, indicating that the interaction between CIP and the carbonized resins was monolayer adsorption. The maximum adsorption capacity fitted by the Langmuir model was 384.4 mg/g at 25 °C. Microstructural analysis showed that the adsorption of CIP on the carbonized resins was a joint effect of H-bonding, ion exchange, and graphite-N adsorption. Computational results signified the strong H-bonding and ion exchange interactions existed between CIP and carbonized resins. The high adsorption and reusability suggest that waste cation exchange resin-based activated carbons can be used as an effective and reusable adsorbent for removing CIP from aqueous solutions. [Display omitted] •Waste cation exchange resins were used to prepare the carbonated resins adsorbent.•The removal of CIP reached 93 % when the dosage of adsorbent was 300 mg/L.•The maximum adsorption capacity fitted by Langmuir equation was 384.4 mg/g at 25 °C.•The graphite-N adsorption, H-bond and ion exchange involved in CIP adsorption.•Theoretical investigations further validated the experimental results.